The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/head.13121
|View full text |Cite
|
Sign up to set email alerts
|

Migraine Subclassification via a Data‐Driven Automated Approach Using Multimodality Factor Mixture Modeling of Brain Structure Measurements

Abstract: Background The current sub-classification of migraine is according to headache frequency and aura status. The variability in migraine symptoms, disease course, and response to treatment suggest the presence of additional heterogeneity or subclasses within migraine. Objective The study objective was to sub-classify migraine via a data-driven approach, identifying latent factors by jointly exploiting multiple sets of brain structural features obtained via magnetic resonance imaging (MRI). Methods Migraineurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
(115 reference statements)
2
16
0
Order By: Relevance
“…Others have reported an association between allodynia and certain subgroups of migraine. 6,27 Given the association between allodynia and central sensitization, 28 it might be expected that allodynia would attenuate HRs for members of classes with pain comorbidities (i.e., respiratory/pain and pain classes). While allodynia attenuated the HR, to a degree, the magnitude of the effect was relatively uniform across comorbidity classes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have reported an association between allodynia and certain subgroups of migraine. 6,27 Given the association between allodynia and central sensitization, 28 it might be expected that allodynia would attenuate HRs for members of classes with pain comorbidities (i.e., respiratory/pain and pain classes). While allodynia attenuated the HR, to a degree, the magnitude of the effect was relatively uniform across comorbidity classes.…”
Section: Discussionmentioning
confidence: 99%
“…2 Increased headache day frequency, medication overuse, depression, and cutaneous allodynia are associated with progression to CM. 3,4 MRI 5,6 and gene association studies 1 have previously identified subgroups of migraine with features predisposing to progression to CM.…”
mentioning
confidence: 99%
“…Recent machine learning studies have focused on the diagnosis of migraine. Machine learning algorithms based on brain resting state functional magnetic resonance imaging (MRI), or morphometric MRI data have been used to identify brain signatures that discriminate migraine patients from controls (17)(18)(19). The functional connectivity of brain regions involved with processing the affective components of pain, like the insula, amygdala, temporal, and frontal lobes, discriminated migraine patients from controls with an accuracy rate of 86%.…”
mentioning
confidence: 99%
“…The altered patterns of functional connections that distinguish migraine patients from controls could represent migraine biomarkers that are further reinforced by recurrent pain (17). On the other hand, an unsupervised machine learning approach was not able to clearly separate migraineurs from healthy controls based upon brain morphometric measures (19). An improvement in classification performance in migraine identification can be achieved integrating functional and structural imaging metrics that disclose complementary information regarding the underlying biological processes (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation